Less than zero - Ellis, Bret Easton 1964- (Vintage contemporaries, 1998)
Returning to Los Angeles from his Eastern college for a Christmas vacation in the early 1980s, Clay "reenters a landscape of limitless privilege and absolute moral entropy, where everyone drives Porsches, dines at Spago, and snorts mountains of cocaine ... A raw, powerful portrait of a lost generation."--Back cover.